ANALISIS RASIO BIAYA DANA DALAM KINERJA KEUANGAN BANK : PENDEKATAN STUDI KASUS INDUSTRI PERBANKAN DI INDONESIA - Agustian Mahendra Putera; Rio Ferdinand Simarmata; Pramesti Pramudita Ektiyas Anggraeni; Renny Oktafia (CV. ALIM'SPUBLISHING, 2024)
The cost of funds ratio is a matrix used to carry out analysis in financial reports to evaluate banking financial performance by connecting various factors that influence the cost of funds ratio. Financial ratio analysis is part of business analysis that assesses a company's prospects and risks. Cost of funds ratio analysis describes the relationship between the amount of money and the company's burden in managing these finances to increase profitability. Cost of funds ratio analysis method. Research was conducted to identify information related to cost of funds ratio analysis in banking. The research results show the significant impact of financial ratio analysis on the financial performance of banking companies in Indonesia. Suggestions include increasing LDR, reducing NPL, controlling operational costs, and improving customer service. It is also recommended that the banking industry be able to reduce the cost of funds ratio regularly to improve its financial performance.